Evaluation of Nutritional Strategies to Reduce Growth Rate of Pigs Beyond 200 lb Body Weight - Z. X. Rao; J. T. Gebhardt; M. D. Tokach; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2020)
A total of 356 finishing pigs (DNA; 241 × 600; initially 196.3 ± 2.43 lb) were used in a44-d growth trial to evaluate nutritional strategies to reduce growth rate of pigs beyond200 lb body weight. A total of 3 diets were manufactured (control, Lys-deficient, andcorn) and arranged into 4 nutritional strategies. In stage 1 (d 0 to 28), pens received oneof two dietary treatments (control or Lys-deficient). Then on d 28, pens of pigs previouslyfed the control diet were separated into 2 groups, one fed the control diet and theother the corn diet. Pens of pigs previously fed the Lys-deficient diet were separatedinto 2 groups, one fed the Lys-deficient diet and the other the corn diet. The controldiet contained 13.0% CP and 0.70% standardized ileal digestible (SID) Lys; the Lys-deficientdiet contained 10.3% CP and 0.50% SID Lys; and the corn diet contained8.1% CP and 0.18% SID Lys. There were 9 to 10 pigs per pen and 9 pens per treatment.Pens were assigned to 1 of the 4 nutritional strategies in a randomized complete blockdesign with initial weight as a blocking factor. In stage one (d 0 to 28), pigs fed theLys-deficient diet had decreased (P<0.001) ADG, F/G, and d 28 BW compared topigs fed the control diet. There was no evidence of difference in ADFI between controland Lys-deficient diet. In stage 2 (d 28 to 44), pigs fed the corn diet had decreased(P<0.05) ADG and poorer (P<0.05) F/G compared to pigs fed the control or Lys-deficientdiets. Pigs fed the Lys-deficient diet in both stages had decreased (P<0.05)ADG and poorer (P<0.05) F/G compared to pigs fed the control diet in both stages.For the overall period (d 0 to 44), pigs fed the Lys-deficient diet (stage 1) then corndiet (stage 2) had decreased (P<0.05) ADG and final BW, and poorer (P<0.05)F/G compared to the three other treatments. There was no evidence of differencefor ADG, F/G, and final BW between pigs fed the Lys-deficient diet in both stagesand pigs fed the control diet (stage 1) then corn diet (stage 2). Pigs of these two treatmentshad decreased (P<0.05) ADG, F/G, and final BW, compared to pigs fed thecontrol diet in both stages. For carcass characteristics, there was no evidence of differencein carcass yield between treatments. Pigs fed the Lys-deficient diet (stage 1) thencorn diet (stage 2) had decreased (P<0.05) HCW, percentage lean, and loin depth,and increased (P<0.05) backfat compared to pigs fed the control diet in both stages.There was no evidence of difference in backfat, loin depth and percentage lean betweenpigs fed the Lys-deficient and corn diet in stage 2. In summary, low dietary Lys levelsreduced the growth rate of pigs beyond 200 lb, which resulted in up to 26 lb difference in final BW. These results allow producers to have flexible strategies to slow growth rateand try to maintain ideal marketing weights to cope with the reduced capacity ofprocessing plants.
Keywords: Finishing pig; growth rate; late finishing; lysine; slow-down program